1994
DOI: 10.1007/bf00305521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1?-hydroxyvitamin D3 on lumbar bone mineral density and vertebral fractures in patients with postmenopausal osteoporosis

Abstract: The effects of 1 alpha-hydroxyvitamin D3 [1 alpha(OH)D3] on bone mineral density, fracture incidence, and bone metabolism were evaluated by a double-blind, placebo-controlled study. Eighty postmenopausal osteoporotic Japanese women (71.9 +/- 7.3 years, mean +/- SD) were randomly assigned to 1 microgram of 1 alpha(OH)D3 daily or inactive placebo for 1 year. All patients were given supplemental calcium (300 mg of elemental calcium daily). Lumbar (L2-L4) bone mineral density (BMD) determined by dual energy X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
88
0
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(104 citation statements)
references
References 23 publications
7
88
0
7
Order By: Relevance
“…This apparent difference may be partly due to the variability in BMD values resulting from the small sample size in our study, or because about one third of our patients were treated with combined use of RLX and ALF, suggesting that RLX in combination with ALF may be potentially more beneficial for bone health than RLX alone. Actually, several clinical studies [9,10] previously showed that ALF reduced bone turnover and prevented vertebral fractures although its effectiveness may be relatively low, and animal-model studies also showed that ALF inhibited bone resorption [11,12] and stimulated formation [11] to increase BMD. Moreover, although native vitamin D plus calcium, but not activated vitamin D, was supplemented in both patients and controls of the previous clinical studies for RLX [1-6], Nuti et al [13] recently reported superiority of ALF compared to native vitamin D plus calcium in increasing lumbar BMD.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent difference may be partly due to the variability in BMD values resulting from the small sample size in our study, or because about one third of our patients were treated with combined use of RLX and ALF, suggesting that RLX in combination with ALF may be potentially more beneficial for bone health than RLX alone. Actually, several clinical studies [9,10] previously showed that ALF reduced bone turnover and prevented vertebral fractures although its effectiveness may be relatively low, and animal-model studies also showed that ALF inhibited bone resorption [11,12] and stimulated formation [11] to increase BMD. Moreover, although native vitamin D plus calcium, but not activated vitamin D, was supplemented in both patients and controls of the previous clinical studies for RLX [1-6], Nuti et al [13] recently reported superiority of ALF compared to native vitamin D plus calcium in increasing lumbar BMD.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] Paradoxically, such beneficial effects are caused by inhibiting osteoclastogenesis. The present review describes the regulation of osteoclast differentiation and possible mechanisms by which active vitamin D compounds suppress bone resorption in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…(14)(15)(16)(17)32) Histomorphometry showed that vitamin D analogues can stimulate bone-formation activity on cortical and trabecular bone surfaces; however, bone-formation activity was best demonstrated at hypercalcemic doses. (14,15) Similarly in clinical studies, skeletal efficacy was demonstrated for vitamin D analogues, including reduction of nonvertebral fractures, (5)(6)(7) but the realization of bone efficacy in the absence of hypercalcemia or hypercalciuria has been difficult to achieve. (6)(7)(8)(9)(10)33) We hypothesized that nonsecosteroidal vitamin D receptor ligands could be synthesized to preferentially modulate skeletal efficacy over hypercalcemic effects in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…(14,15) Similarly in clinical studies, skeletal efficacy was demonstrated for vitamin D analogues, including reduction of nonvertebral fractures, (5)(6)(7) but the realization of bone efficacy in the absence of hypercalcemia or hypercalciuria has been difficult to achieve. (6)(7)(8)(9)(10)33) We hypothesized that nonsecosteroidal vitamin D receptor ligands could be synthesized to preferentially modulate skeletal efficacy over hypercalcemic effects in vivo. Additionally, we hypothesized that a synthetic compound could have other potential benefits to the elderly, such as improved neuromuscular function, anti-inflammatory/immunomodulation properties, inproved skin quality, and prevention of breast, colon, and prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation